Mitigasi Kemiskinan Ekstrem dengan Pendekatan Community Based Development di Desa Bubeya Kecamatan Suwawa Kabupaten Bone Bolango, Provinsi Gorontalo - Ramlan Amir Isa; Cristian Polamolo; Alzahra Salsabila Walangadi (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2026)
Extreme poverty remains a critical and systemic issue in regional development paradigms, prominently within Bone Bolango Regency. Although the aggregate number of poor residents has shown a marginally declining trend, the poverty depth and severity indexes have paradoxically increased over the past two years, indicating growing inequality. Bubeya Village, situated in Suwawa District, epitomizes this socioeconomic challenge with major hurdles encompassing the low level of family economic empowerment, sub-optimal utilization of natural resources, and the fragile capacity of local institutions. The Community Service Program (Kuliah Kerja Nyata / KKN) Thematic Phase II of Universitas Negeri Gorontalo was strategically implemented utilizing the Community Based Development (CBD) approach, a methodology that strictly emphasizes active community participation as the central actor of sustainable development. The interventions were methodically executed through four primary stages, preparation, implementation, evaluation, and follow-up, actively engaging residents, village officials, and marginalized community groups. The program was deliberately focused on two interrelated pillars: bolstering the local economic resilience through the innovative utilization of natural resources and proactively preventing social impediments, particularly the prevalent issue of early marriage. A cornerstone of the economic innovation introduced was the extraction and utilization of lemongrass and lemon leaves to manufacture high-quality aromatherapy candles. This specific product was positioned as a tangible model illustrating how raw agricultural outputs can be effectively processed into value-added commodities with broader, lucrative market opportunities. Concurrently, the prevention of early marriage was comprehensively addressed through interactive socio-educational discussions in collaboration with BKKBN, highlighting the absolute necessity of higher education, economic independence, and youth preparedness for future challenges. Through these multifaceted activities, the Bubeya Village community acquired a renewed perspective that effective poverty alleviation strategies must inherently amalgamate economic growth initiatives with the fundamental improvement of human capital quality. Ultimately, this program has generated a dual-impact framework: stimulating local MSME growth through novel business opportunities while simultaneously cultivating profound social awareness regarding the detrimental impacts of early marriage. These comprehensive outcomes are projected to serve as a foundational catalyst towards an inclusive and sustainable community independence.